A new species of the genus Trigonura Sichel, 1865 (Hymenoptera: Chalcididae) from Vietnam - Long, Khuat Dang; Hiep, Nguyen Duc; Hoa, Dang Thi; Ngat, Tran Thi (Academia Journal of Biology, 2019)
Based on the specimens of chalcid parasitoid wasps collected by malaise traps set in fruit orchards in the adjacent area of Ha Noi city from 2018–2019, one new species of the genus Trigonura, T. vietnamica Long, sp. n., was described and illustrated. Two species of this genus from Vietnam are keyed, the comparative characters of the new species were also given to compare with two similar species from the Oriental Region, T. indica Narendran and T. luzonensis Narendran.